Role of teledermatology in the management of dermatological diseases among marine workers: A cross-sectional study comparing general practitioners and dermatological diagnoses - Di Canio, Marzio; Burzi, Lorenza; Ribero, Simone; Amenta, Francesco; Quaglino, Pietro (Frontiers in Medicine, 2022)
Background. Diagnosis and treatment of seaworkers’s skin disease is an unmet need. The purpose of this study is to highlight how remote management of dermatological conditions appear inadequate in this scenario. Objective. To identify the most epidemiology of seafarers diseases and to analyse the adequacy of medical assistance in the diagnosis of dermatological maritime diseases. Material and methods. 420 cases of requests for dermatological diseases received by the Telemedical Maritime Assistance Service of the CIRM in a referral year were included in this cross-sectional study. All pictures of cutaneous lesions had been submitted to both CIRM doctors and an expert dermatologist who provided their diagnosis. Results. The most frequent diagnosis in both groups were infectious or inflammatory skin diseases. Main differences are represented by the amount of “unclassified dermatitis” or descriptive diagnosis, such as “cutaneous eruption“ which were the most frequent diagnosis of CIRM doctors (p: <0.05 and p>0.0001). In these cases, Cohen's K was <0.5 consistent with low concordance between dermatologic diagnosis and CIRM diagnosis. Conclusion and relevance. Our study emphasizes the magnitude of dermatological diseases in the maritime sector, although often underestimated, and highlights the difficulty in their diagnosis for doctors on call that need more training of the specific dermatological issues.